Participação do receptor TRPA1 em modelos de ataque agudo de gota em roedores - Santos, Gabriela Trevisan dos (2013)
Gout is a prevalent form of inflammatory arthritis, which leads to patients poor quality of life. Acute gout attacks produce severe joint pain and inflammation associated with oxidative stress induction. This pathology is provoked by the accumulation of monosodium urate (MSU) crystals, but the underlying pain mechanisms in acute gout attacks are still poorly understood. The transient potential receptor ankyrin 1 (TRPA1) is a sensor for endogenous oxidant compounds, such as hydrogen peroxide (H2O2), found in peptidergic sensory fibers associated to inflammatory pain. The goal of this study was to explore the TRPA1 role in two models of monosodium urate (MSU) crystals-induced inflammation and nociception in rats and mice. We found that TRPA1 antagonism (HC-030031 or camphor), TRPA1 gene deletion or defunctionalization by capsaicin pretreatment of peptidergic TRPexpressing primary sensory neurons markedly decreased MSU-induced nociception and edema after intraplantar (i.pl.) or intra-articular (i.a.) injection. In addition to these neurogenic effects, MSU increased H2O2 levels in the injected tissue, an effect that was abolished by the H2O2-detoxifing, catalase enzyme. TRPA1 immunoreactivity in sciatic nerve and the levels of calcitonin gene related peptide (CGRP) in the synovial tissue were also increased by MSU. H2O2 i.pl. or i.a. injection mimicked MSU, causing nociception and edema prevented by TRPA1 antagonism. Moreover, TRPA1 blockage abrogated the increase in neutrophil infiltration and interleukin-1β elicited by MSU. Our results suggest that MSU-injection increases tissue H2O2 thereby stimulating TRPA1 on sensory nerve endings to produce inflammation and nociception. Thus, TRPA1 may be explored as a valuable target in acute gout management.